Acute chest pain and dyspnoea as clinical presentation of primary membranous nephropathy. A case report and literature review - Poggiali, Erika; Borio, Giorgia; Magnacavallo, Andrea; Vercelli, Andrea; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2022)
Membranous nephropathy (MN) is the commonest cause of nephrotic syndrome (NS) in adult male patients worldwide. Most of the cases (80%) are idiopathic (primary MN, PMN), whereas about 20% are associated with autoimmune diseases, malignancies or exposures (secondary MN). PMN is a kidney-specific autoimmune glomerular disease mediated by antibodies to the M-type phospholipase A2 receptor (anti-PLA2R) (85%), thrombospondin type 1 domain containing 7A (THSD7A) (3–5%), or by other still unidentified mechanisms (10%). Most of the patients with PMN present with NS (80%). Clinical course of PMN is characterised by spontaneous remissions (40%) and relapses (15-30%). One third develop end-stage renal disease (ESRD) within 5 to 15 years from the onset. Anti-PLA2R/THSD7A antibodies levels correlate with proteinuria, clinical course, and outcomes. The treatment still remains matter of debate. Hypertension, proteinuria, and hyperlipidaemia must be treated in all patients. Immunosuppressive therapy is indicated in patients with elevated anti-PLA2R/THSD7A levels and proteinuria >3.5 g/d at diagnosis. With proper management, only 10% or less will develop ESRD over the subsequent 10 years. Here we report a case of a 34-year-old male patient with a ten-year history of asymptomatic PMN, treated with ACE-inhibitors, who presented to our emergency room for acute chest pain and exertional dyspnoea due to ESRD that required urgent dialysis. (www.actabiomedica.it)